2017
DOI: 10.1161/jaha.116.004488
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte‐Specific Enhancement of Angiotensin II Type 1 Receptor‐Associated Protein Ameliorates Diet‐Induced Visceral Obesity and Insulin Resistance

Abstract: BackgroundThe renin–angiotensin system has a pivotal role in the pathophysiology of visceral obesity. Angiotensin II type 1 receptor (AT1R) is a major player in the signal transduction of the renin–angiotensin system, and the overactivation of this signaling contributes to the progression of visceral obesity. We have shown that the AT1R‐associated protein (ATRAP) promotes AT1R internalization from the cell surface into cytoplasm along with the suppression of overactivation of tissue AT1R signaling. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
6
37
0
Order By: Relevance
“…However, ATRAP exerts no evident influence on the physiological AT1R signaling pathway. For example, the phenotype of ATRAP transgenic mice with overexpression of ATRAP in cardiovascular tissue is similar to that of their littermate WT control mice under nonstimulating conditions . In the current study, there were no significant differences in blood pressure, cardiovascular injury, and glucose/fat metabolism profiles between aged ATRAP‐KO and WT mice (Figure ; Table).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, ATRAP exerts no evident influence on the physiological AT1R signaling pathway. For example, the phenotype of ATRAP transgenic mice with overexpression of ATRAP in cardiovascular tissue is similar to that of their littermate WT control mice under nonstimulating conditions . In the current study, there were no significant differences in blood pressure, cardiovascular injury, and glucose/fat metabolism profiles between aged ATRAP‐KO and WT mice (Figure ; Table).…”
Section: Discussionsupporting
confidence: 52%
“…ATRAP in cardiovascular and adipose tissue can inhibit hyperactivation of tissue AT1R signaling caused by certain pathological stimuli, such as chronic Ang II infusion or dietary loading, and improve cardiovascular disturbances and insulin resistance . However, ATRAP exerts no evident influence on the physiological AT1R signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II type 1 receptor (AT1R)‐associated protein (ATRAP/Agtrap) is a transmembrane protein localized to the plasma membrane and perinuclear vesicular structures and was originally identified as a low‐molecular‐weight protein that binds to the carboxyl‐terminal domain of AT1R . The strongest expression of ATRAP was found in renal tubules of kidneys, and it also was found in the heart, kidneys, vascular smooth muscle cells, and adipose tissues . Previous studies showed us that ATRAP could enhance the constitutive internalization of AT1R and suppress the activation of angiotensin II in order to negatively regulate angiotensin II signaling and selectively suppress Ang II‐mediated pathological responses .…”
Section: Discussionmentioning
confidence: 99%
“…ATRAP‐dependent signalling can suppress the overactivation of adipose AT 1 R signalling, mediated by G protein and β‐arrestin. This action can prevent hypertrophy, diet‐induced visceral obesity and insulin resistance and, hence, play a compensatory role .…”
Section: Ras In the Regulation Of White Adipose Tissue Functioningmentioning
confidence: 99%